DIGITAL CIVILITY INDEX IN THE ERA OF INFORMATION TECHNOLOGY: A CASE STUDY OF HIGHER EDUCATION MUSLIM STUDENTS IN YOGYAKARTA - Iin Fadila Ramadhani; Krismono (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
Globalization that occurs requires people to be literate about technology. This should not affect the public in using the internet. This research is a descriptive research through interview, surveys, and observations with Muslim students at universities in Yogyakarta as research subjects. Compared to other countries in Asia, Indonesia is the most impolite country based on a survey conducted by Microsoft. This figure is higher when compared to the previous year. The amount of hoax and fraud news influences the level of public decency. From the resulting sample, as many as 20% have spoken harshly on social media and the other 80% have never, this difference is influenced by the environment around each youth which is different. With the majority of Muslim students not being able to say impolite sentences, it needs to be maintained, whereas if they still say harsh sentences/discrimination in cyberspace, it needs to be minimized through cooperation by all levels of society, from families, schools to government agencies.